Sampah Bernilai: Edukasi Literasi Sampah Dan Kerajinan Sampah Untuk Lingkungan Berkelanjutan - Adisti Nur Aisyah; Agus Riyanto; Evana Sanyya; Candra Reza Kurniawan; Sintia Yohana Aksah; Nabilatul Maulisa; Rizky Pratama; Inten Maya Lestari; Tisna Fatkhatun Khasanah; Estri Utaminingsih; Mamluatul Hikmah; Kharisma Ibnu Rasyid; Jayanti Nofiana Nur (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The project "Valuable Waste: Waste Literacy Education and Waste Craftsmanship for Sustainable Environment" aims to raise environmental awareness and creative skills among children at the Al Ishlah Hidayatullah Orphanage. Through observation, interviews, and participatory approaches, this project successfully engaged the children in educational activities on waste literacy and crafting from plastic waste. The results of the project demonstrated an increase in the children's understanding of waste management and their ability to recycle waste into valuable products. Items such as keychains made from bottle caps and trash bins from plastic gallon containers not only helped reduce waste but also provided aesthetic and economic value. The active participation of the children and the support from project partners contributed to the success of this sustainable program.